2005
DOI: 10.1126/science.1104226
|View full text |Cite
|
Sign up to set email alerts
|

Porous Semiconductor Chalcogenide Aerogels

Abstract: Chalcogenide aerogels based entirely on semiconducting II-VI or IV-VI frameworks have been prepared from a general strategy that involves oxidative aggregation of metal chalcogenide nanoparticle building blocks followed by supercritical solvent removal. The resultant materials are mesoporous, exhibit high surface areas, can be prepared as monoliths, and demonstrate the characteristic quantum-confined optical properties of their nanoparticle components. These materials can be synthesized from a variety of build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
373
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 550 publications
(382 citation statements)
references
References 25 publications
9
373
0
Order By: Relevance
“…At high dilutions, the fractal structure of the aggregates is independent of the initial concentration of the aggregating particles, but starts to increase when the density becomes sufficient to form percolating networks with a fractal dimension of d perc f = 2.5. In principle, the model provides a reasonable scenario of nanoparticle aggregation emerging, for instance, as one a) Electronic mail: swetlana.jungblut@tu-dresden.de of the steps in the aerogel production [14][15][16][17][18][19][20][21] , in which the destabilization of nanoparticles suspended in a solution induces their aggregation into disordered networks. The recent advances in nanotechnology and the expansion of the research associated with the topic of nanoparticle aggregation revealed, however, some deficiencies of the model.…”
Section: Introductionmentioning
confidence: 99%
“…At high dilutions, the fractal structure of the aggregates is independent of the initial concentration of the aggregating particles, but starts to increase when the density becomes sufficient to form percolating networks with a fractal dimension of d perc f = 2.5. In principle, the model provides a reasonable scenario of nanoparticle aggregation emerging, for instance, as one a) Electronic mail: swetlana.jungblut@tu-dresden.de of the steps in the aerogel production [14][15][16][17][18][19][20][21] , in which the destabilization of nanoparticles suspended in a solution induces their aggregation into disordered networks. The recent advances in nanotechnology and the expansion of the research associated with the topic of nanoparticle aggregation revealed, however, some deficiencies of the model.…”
Section: Introductionmentioning
confidence: 99%
“…ions or molecules). The former has been adapted across noble metal (16,(18)(19)(20)(21) , metal chalcogenide (22)(23)(24)(25)(26) , and metal oxide (27)(28)(29)(30)(31) systems, but this method is prone to fuse NCs during assembly and consequently limits the realization of size and shape-dependent NC optical properties (i.e., PL and LSPR) within the gels. While gelation via chemical bridging is a viable strategy to mitigate NC fusing, translating this approach across NC materials requires customizing surface functional groups for specific NC compositions, so far limited to metal chalcogenide NCs (32,33) and Au NPs (17) .…”
Section: Introductionmentioning
confidence: 99%
“…[88] Nowadays, a wide range of inorganic materials can be processed into nanoparticle-based aerogels including metal chalcogenides (CdS, CdSe, CdTe, PbS, ZnS, etc. ), [84,[88][89][90][91][92][93][94][95][96] metals (Pd, Pt, Au, Ag, etc. ), [97][98][99][100][101] their oxides (TiO 2 , [102][103][104][105][106] Y 2 O 3 , [81] BaTiO 3 , [82] InTaO 4 , [107] SrTiO 3 , [87] Y 3 Al 5 O 12 , [108] etc.…”
Section: Disordered Porous Structuresmentioning
confidence: 99%
“…Controlled destabilization can be accomplished by means of additives such as acids, bases, electrolytes, [99,110] complexing agents, [96,[114][115][116] ligand strippers, [85,88,97] or non-solvents. [82,[102][103][104][105]108] Another possibility is the use of non-additive triggers such as temperature, [82,83,100,[102][103][104][105] irradiation, [84,106] mechanical methods such as centrifugation, [81,107,117] ultrasonic treatment, [82] or electrochemical methods. [118] The choice of trigger depends primarily on the type of stabilization (electrostatic or steric).…”
Section: Disordered Porous Structuresmentioning
confidence: 99%